Influence of SCN1A Gene Mutation on Age of Onset of Febrile Seizures in GEFS+ - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Twelve multigenerational families with the generalized epilepsy and febrile seizure plus (GEFS+) syndrome and a known clinically relevant epilepsy gene mutation were examined for age of onset of febrile seizures (FS or FS+), in a study at the University of Melbourne, Australia, and centers in the Netherlands and Israel.